Dalcroze’s Rhythmics: educational aspects and inclusive perspectives - Sgambelluri, Rosa (Formazione & insegnamento, 2018)
Èmile Jaques Dalcroze claims the centrality of the body, as a forge, a workspace where the music has a shape and sense and where it imagines a continuous exchange between control of movements and the perception of sound events, starting from rhythmic ones. The body, therefore, is involved entirely in the range of its functions, in breathing, in the control of muscular tension, in balance and in the performed movements Dalcroze’s Rhythmics does not stop at the rhythmic dimension of music, but goes so far as to establish the complete musical morphology on the body. It also sees body movement as a reference point for musical performance where the body itself covers the role of intermediary between sound and thought such as it becomes a feelings instrument. The Dalcroze method is widely used also in the didactic context, where it represents for the disabled students an important inclusive space where to enhance their specificity and potential.